Making healthcare decisions for terminally ill adults and elderly in rural Bangladesh: an application of social autopsy - Nurul Alam; Hafizur Rahman Chowdhury; Sayed Saidul Alam; Taslim Ali; Peter Kim Streatfield; Ian Douglas Riley; Alan D Lopez (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background This study investigated healthcare decision-making surrounding terminal illnesses of adults and elderly persons (aged 15 years or more), who later died at home, hospitals, or in-transit, in a rural, low-income area of Bangladesh where out-of-pocket health expenditure is very high. # Methods There were 1330 adult and elderly deaths in Matlab Health and Demographic Surveillance site in 2013. To record how decisions were made and implemented when caring for terminal illness, and how treatment-related costs were managed, the main caregivers of 69 randomly selected persons who died at home, 74 who died in hospitals, and 11 who died in-transit were interviewed with a social autopsy questionnaire in 2014. Differences between groups were tested by χ^2^ for significance at *P* \<0.05. # Results Those who died at home were sick for longer periods than those who died in hospitals or in-transit. During terminal illness, 33% of the home deaths were admitted, but discharged from hospitals prior to death for no chance of cure (52%) or financial constraints (17%). The reasons for 67% of home deaths not being admitted to a hospital were no chance of cure (28%), misjudgment of illness severity (21%), too short duration of illness (20%), or financial constraints (17%). For hospital deaths, final decisions were mostly made by family members (95%) as opposed to physicians (5%) for cure of serious illness (93%). Hospitals were chosen considering quality of care (59%), distance (36%), known doctors (35%) or referral (29%). After hospitals were chosen, 42% of hospitalizations were delayed due to lack of money (33%), misjudgment of illness severity (31%), or lack of someone to accompany the patient (31%). Payment of hospital costs included family savings (87%), borrowing from relatives (46%) or borrowing from moneylenders (6%). # Conclusions Healthcare decisions for terminally ill adults and elderly persons were influenced by the caregivers' assessment of chances of cure, judgment of illness severity and financial constraints. Improving understanding of illness severity and lowering direct out-of-pocket expenditures may help patients who have a reasonable chance of cure receive care in a hospital.